2016
DOI: 10.4172/2157-7412.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds as Therapeutic Agents in the Treatment Cystic Fibrosis

Abstract: The recent FDA approval of two drugs to treat the basic defect in cystic fibrosis has given hope to patients and their families battling this devastating disease. Over many years, with heavy financial investment from Vertex Pharmaceuticals and the Cystic Fibrosis Foundation, pre-clinical evaluation of thousands of synthetic drugs resulted in the production of Kalydeco and Orkambi. Yet, despite the success of this endeavor, many other compounds have been proposed as therapeutic agents in the treatment of CF. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…Therefore, anti-in ammatory treatments are an inevitable therapy for CF patients. Curcumin is the main ingredient in turmeric with a substantial impact on the reduction of in ammatory factors (8) (9). Previous ndings have indicated that curcumin could correct the CFTR protein function (corrector) in the F508del mutation, which is associated with the CFTR protein misfolding (10).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Therefore, anti-in ammatory treatments are an inevitable therapy for CF patients. Curcumin is the main ingredient in turmeric with a substantial impact on the reduction of in ammatory factors (8) (9). Previous ndings have indicated that curcumin could correct the CFTR protein function (corrector) in the F508del mutation, which is associated with the CFTR protein misfolding (10).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…6,48 PCs hold the promise of being able to reduce the severity of several genetic diseases, but it is important to note that the number of PCs described for different targets is low. For instance, in cystic fibrosis (CF), a number of PCs and PRs that might rescue CF transmembrane conductance regulator (CFTR) have recently been identified, 34,[49][50][51] one of which is the PR roscovitine, which is involved in calcium regulation. 52 The use of therapeutic autophagy inducers has also been tested in CF.…”
Section: Pharmacological Chaperonesmentioning
confidence: 99%
“…Curcumin has been reported to correct localization of ATP7B -R778L and to facilitate Cu efflux from patient-derived HLCs. However, in phase 1 clinical trials for CFTR correction, dietary curcumin was found to have very poor bioavailability and very low serum concentration[ 15 ]. Thus, the efficacy of this corrector for WD treatment remains questionable.…”
Section: Correction Of Dysfunctional Atp7bmentioning
confidence: 99%